A bead‐based assay in the work‐up of suspected platelet alloimmunization. Issue 1 (6th November 2015) - Cooper, Nina; Bein, Gregor; Heidinger, Kathrin; Santoso, Sentot; Sachs, Ulrich J.
Abstract : BACKGROUND: Alloantibodies against human platelet antigens (HPAs) are of clinical significance in immune‐mediated thrombocytopenia such as fetal/neonatal alloimmune thrombocytopenia (FNAIT), posttransfusion purpura, and platelet (PLT) transfusion refractoriness. The gold standard for the detection of these antibodies is the monoclonal antibody immobilization of PLT antigens (MAIPA) assay. Both requirement of typed donor PLT panels and technical expertise often restrict its use to reference laboratories. STUDY DESIGN AND METHODS: An easy‐to‐use, bead‐based assay (BBA) has been introduced recently. In this study, we compared MAIPA and BBA test results for 126 serum samples from women who gave birth to a child with FNAIT including rare HPA specificities (n = 111) and from patients with PLT transfusion refractoriness (n = 15). RESULTS: For sera with defined allospecificities, the number of BBA false‐negatives was 12 of 126, or 9.5%, and the number of BBA false‐positives (i.e., detection of additional specificities) was two of 126, or 1.6%. BBA had major problems in detecting antibodies against HPA‐3a (3/15 undetected = 20% failure rate) and HPA‐3b (5/6 undetected = 83.3% failure rate), but performed well in detecting typical FNAIT‐ or PLT transfusion refractoriness–associated antibodies including HPA‐1a (35/35 = 100%), HPA‐1b (15/15 = 100%), HPA‐5b (22/24 = 91.6%), and glycoprotein IV (6/6 = 100%). CONCLUSION: BBA might be a useful and time‐saving tool in the initial laboratory work‐up of suspected PLT alloimmunization when an appropriate algorithm ensures follow‐up investigation of BBA‐negative sera.